(untitled) (Scientific journal of the Fergana State University, 2025)
This study explores the cognitive and lexical characteristics of communicative reading competence through a combination of qualitative and quantitative methods. Findings reveal that communicative competence is often developed through the use of linguo-didactic methods that develop reading skills to improve comprehension. Learning a foreign language for professional purposes makes it necessary to learn terms related to this field. The morphological complexity, semantic relationships, and syntactic roles of these terms underscore their importance in technical communication. Educational exercises targeting these features can improve terminological competence, while professionals can benefit from a deeper understanding of these dimensions for better communication and documentation practices.